4(3z-1)-4(z+8)=5(z+1)

Simple and best practice solution for 4(3z-1)-4(z+8)=5(z+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3z-1)-4(z+8)=5(z+1) equation:


Simplifying
4(3z + -1) + -4(z + 8) = 5(z + 1)

Reorder the terms:
4(-1 + 3z) + -4(z + 8) = 5(z + 1)
(-1 * 4 + 3z * 4) + -4(z + 8) = 5(z + 1)
(-4 + 12z) + -4(z + 8) = 5(z + 1)

Reorder the terms:
-4 + 12z + -4(8 + z) = 5(z + 1)
-4 + 12z + (8 * -4 + z * -4) = 5(z + 1)
-4 + 12z + (-32 + -4z) = 5(z + 1)

Reorder the terms:
-4 + -32 + 12z + -4z = 5(z + 1)

Combine like terms: -4 + -32 = -36
-36 + 12z + -4z = 5(z + 1)

Combine like terms: 12z + -4z = 8z
-36 + 8z = 5(z + 1)

Reorder the terms:
-36 + 8z = 5(1 + z)
-36 + 8z = (1 * 5 + z * 5)
-36 + 8z = (5 + 5z)

Solving
-36 + 8z = 5 + 5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-5z' to each side of the equation.
-36 + 8z + -5z = 5 + 5z + -5z

Combine like terms: 8z + -5z = 3z
-36 + 3z = 5 + 5z + -5z

Combine like terms: 5z + -5z = 0
-36 + 3z = 5 + 0
-36 + 3z = 5

Add '36' to each side of the equation.
-36 + 36 + 3z = 5 + 36

Combine like terms: -36 + 36 = 0
0 + 3z = 5 + 36
3z = 5 + 36

Combine like terms: 5 + 36 = 41
3z = 41

Divide each side by '3'.
z = 13.66666667

Simplifying
z = 13.66666667

See similar equations:

| 3-2(x+2)=3 | | 20*6-18*6-6=12 | | 1/2x^2-36=0 | | 5(2x-11)=3x+9 | | 3/5.22 | | 4(x+1)-2(-x-1)=0 | | 12+10=10+12 | | 6x-30+1=0 | | 3-7(-x+5)=2x+5 | | 40(x)+60(y)=1700 | | 8(x-1)-2(3x+4)=0 | | 4x^2+9y^2-8x-54y-59=0 | | ln(3x+2)-ln(2)=1 | | ln(x^3+x^2-2)=ln(x-1)(x^2-1) | | X+2x-1=11 | | 10x-24=4x | | x^2=8-9x | | 3.25n+2=3n+6 | | -3x+6=-6x | | 5y+11=(3y+7) | | 4w(7w+3)=0 | | -2x+9x+5=0 | | 4x^4+36x^3= | | (t+2)(6t+1)=0 | | 7.5x-2.5=20.0 | | 11x+37=90 | | 36x4/9= | | 4(3x-2)+3x-7=0 | | 22-30x-1=-63 | | 4ab=16 | | (2y+2)(2y-4)=0 | | 15=0.6(10+n) |

Equations solver categories